Knowledge on the HPV vaccine among university students - Denise Leite Maia Monteiro; Leila Cristina Soares Brollo; Tayná Pinheiro de Souza; Joanna Rangel Peixoto dos Santos; Gildásio Rocha Santos; Tatiane Correa; Julie Teixeira da Costa; Marco Aurélio Pinho de Oliveira; Alexandre José Baptista Trajano (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
ABSTRACT The objective is to evaluate knowledge on HPV vaccine and its use among university students. This is a cross-sectional study with 301 participants, of which 202 medical students from UERJ and UNIFESO (101 freshmen = M1 and 101 from the 6th year = M2) and 99 UERJ literature students (50 freshmen = L1 and 49 of the last year = L2). Information was obtained by questionnaires. Input and statistical analysis were carried out with the EPI-INFO 3.5.2 Program. Results showed that, among medical students, 21% of M1 and 16% of M2 used the HPV vaccine (p=0.35), mostly adopted by women (M1=29.7% and M2=21.3%) than men (M1=5.4% and M2=7.5%). Similarly, female students showed more interest in using the vaccine (M1=85.1% and M2=80%) than male (M1=56.2% and M2=20.5%). Among literature students, only women received the vaccine (L1=6.5% and L2=22.2%) and no men were vaccinated (p=0.04). More women expressed interest in receiving the vaccine than men (♀ L1=76%, L2=65% and ♂, L1=47%, L2=40%). Comparison among genders regardless of the course showed that the vaccination rate is higher among women (p<0.001), as is the interest in being vaccinated (p=0.004). We concluded that the majority of male university students know less about the HPV vaccine than the female ones, use less and are less interested in being vaccinated, in all the groups interviewed. Vaccination coverage is low among the university population and is higher among medical students.